160k views
3 votes
5 - 7k = -4(k + 1) - 3​

User Hansmaad
by
5.5k points

2 Answers

4 votes
Step 1: Simplify both sides of the equation.
5

7
k
=

4
(
k
+
1
)

3
5
+

7
k
=
(

4
)
(
k
)
+
(

4
)
(
1
)
+

3
(Distribute)
5
+

7
k
=

4
k
+

4
+

3

7
k
+
5
=
(

4
k
)
+
(

4
+

3
)
(Combine Like Terms)

7
k
+
5
=

4
k
+

7

7
k
+
5
=

4
k

7
Step 2: Add 4k to both sides.

7
k
+
5
+
4
k
=

4
k

7
+
4
k

3
k
+
5
=

7
Step 3: Subtract 5 from both sides.

3
k
+
5

5
=

7

5

3
k
=

12
Step 4: Divide both sides by -3.

3
k

3
=

12

3
k
=
4
Answer:
K=4
User Pancake
by
5.7k points
2 votes

Answer:

5 - 7k = -4(k + 1) - 3​

5 - 7k = -4k - 4 - 3​

7k + 4k = - 4 - 3​ -5

11k = -12

k = -12/11

~batmans wife dun dun dun...

User MVZ
by
4.6k points